Sistem Informasi Pencatatan Transaksi Obat pada UPTD Instalasi Farmasi Kota Tanjungbalai - Raja Syahmuda Siregar; Bambang Irwansyah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
This study aims to design a drug inbound and outbound transaction application that can improve the effectiveness and efficiency of drug data management at the UPTD Pharmacy Installation of Tanjungbalai City. The research method used in this study is a descriptive qualitative method with a case study approach. Data collection was carried out through direct observation at the research location, interviews with pharmacy staff, and documentation studies of documents related to drug management. The data obtained were then analyzed to identify weaknesses in the current system and determine the system requirements to be designed. The results of the study indicate that the existing manual recording system has not been able to support optimal drug management because it is less effective and prone to errors. The drug inbound and outbound transaction application designed in this study can assist pharmacy staff in recording incoming and outgoing drug data, monitoring drug stock in real-time, and generating reports automatically.